Biocatalysts composed by lipase from thermomyces lanuginosus immobilized on superparamagnetic nanoparticles: design and application of lipase-nanoparticle biocatalysts in the synthesis of compounds used in different industrial fields - Bezerra, Rayanne Mendes (2018)
Lipase from Thermomyces lanuginosus (TLL) was immobilized on superparamagnetic iron oxide (Fe3O4) nanoparticles (SPMN) by different methods. Initially, the nanoparticles were prepared by the coprecipitation method. Then, the surface of magnetite was functionalized with polymers: 3-aminopropyltriethoxysilane (APTES) or branched polyethylenimine (PEI). Therefore, the enzyme immobilization was performed by two ways: by adsorption or by covalent attachment. In the adsorption way, the enzyme was immobilized by ionic affinity to the polymers attached to the SPMN surface. Previously the immobilization by covalent attachment, the support was activated with glutaraldehyde (GA) or divinylsulfone (DVS). Naturally, lipases catalyze the hydrolysis reactions. Thus, the developed biocatalysts were applied in some hydrolysis reactions of economic interest, for example, in the synthesis of a medicament precursor from the kinetic resolution of a racemate, obtaining the maximum conversion (50%) even after the second reaction cycle. However, lipases are able to catalyze esterification reactions in organic media; thus, the biocatalysts obtained after activation with DVS were applied in the esterification reaction of benzyl alcohol, obtaining up to 61% conversion after the seventh reaction cycle. Moreover, the preparations were characterized by different analysis: X-ray diffraction, vibrating sample magnetometry, infrared vibrational spectroscopy, zeta potential, among others. The SPMN presented superparamagnetic behavior even after the different enzymatic immobilization processes. The application conditions of the biocatalysts were also defined through studies of thermal, organic solvent, storage and operational stabilities. The DVS preparations had excellent operational stability, exhibiting more than 50% of the initial catalytic activity even after ten reaction cycles. On the other hand, the GA preparations presented greater thermal stability, reaching more than 7 hours of half-life at pH 7.0 at 70 °C. In general, these biocatalysts are thermostable, have high catalytic efficiency and good operational durability when applied under ideal reaction conditions. In addition, the economic interest reactions carried out in this work showed the potential applications of the developed biocatalysts in the pharmaceutical, cosmetic, biotechnology and fine chemical industries.